2022
DOI: 10.3390/jpm12101695
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure Wound Therapy for the Treatment of Fournier’s Gangrene: A Rare Case with Rectal Fistula and Systematic Review of the Literature

Abstract: Fournier’s gangrene (FG) is a Necrotizing Soft Tissue Infection (NSTI) of the perineal region characterized by high morbidity and mortality even if appropriately treated. The main treatment strategies are surgical debridement, broad-spectrum antibiotics, hyperbaric oxygen therapy, NPWT (Negative Pressure Wound Therapy), and plastic surgery reconstruction. We present the case of a 50-year-old woman with an NSTI of the abdomen, pelvis, and perineal region associated with a rectal fistula referred to our departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…randomized controlled trials are necessary to support the effectiveness of NPWT. 10 The study conducted by Agwu et al concluded that in resource-constraint setting, prompt and adequate resuscitation, aggressive debridement, use of hypertonic saline bath and appropriate broad-spectrum antibiotics give favourable outcome. 11 Another study concluded that treatment is started with fluid resuscitation, broad-spectrum antibiotics and aggressive surgical debridement.…”
Section: Discussionmentioning
confidence: 99%
“…randomized controlled trials are necessary to support the effectiveness of NPWT. 10 The study conducted by Agwu et al concluded that in resource-constraint setting, prompt and adequate resuscitation, aggressive debridement, use of hypertonic saline bath and appropriate broad-spectrum antibiotics give favourable outcome. 11 Another study concluded that treatment is started with fluid resuscitation, broad-spectrum antibiotics and aggressive surgical debridement.…”
Section: Discussionmentioning
confidence: 99%
“…Negative pressure wound therapy can remove tissue exudate, reduce local edema, enhance neovascularization, and improve the tissue's natural self-healing. [43,44] Conversely, hyperbaric oxygen therapy improves tissue perfusion, promotes angiogenesis and fibroblast proliferation, and increases collagen synthesis and oxygen levels in tissues. [45] Four major questions can be raised in this case.…”
Section: Discussionmentioning
confidence: 99%